Toxic acrolein production due to Ca2+ influx by the NMDA receptor during stroke. (January 2016) - Nakamura, Mizuho; Uemura, Takeshi; Saiki, Ryotaro; Sakamoto, Akihiko; Park, Hyerim; Nishimura, Kazuhiro; Terui, Yusuke; Toida, Toshihiko; Kashiwagi, Keiko; Igarashi, Kazuei
Abstract: Background and purpose: N -Methyl-d -aspartate (NMDA) receptors have a high permeability to Ca 2+, contributing to neuronal cell death after stroke. We recently found that acrolein produced from polyamines is a major toxic compound during stroke. Thus, it was determined whether over-accumulation of Ca 2+ increases the production of acrolein from polyamines in a photochemically-induced thrombosis mouse model of stroke and in cell culture systems. Methods: A unilateral infarction was induced in mouse brain by photoinduction after injection of Rose Bengal. The volume of the infarction was analyzed using the public domain National Institutes of Health image program. Protein-conjugated acrolein levels at the locus of infarction and in cells were measured by Western blotting. Levels of polyamines were measured by high-performance liquid chromatography. Results: When the size of brain infarction was decreased by N 1, N 4, N 8 -tribenzylspermidine, a channel blocker of the NMDA receptors, levels of Ca 2+ and protein-conjugated acrolein (PC-Acro) were reduced, while levels of polyamines were increased at the locus of infarction. When cell growth of mouse mammary carcinoma FM3A cells and neuroblastoma Neuro2a cells was inhibited by Ca 2+, the level of polyamines decreased, while that of PC-Acro increased. It was also shown that Ca 2+ toxicity was decreased in an acrolein toxicity decreasing FM3A mutant cells recently isolated. In addition, 20–40 μM Ca 2+ caused the release of polyamines from ribosomes. The results indicate that acrolein is produced from polyamines released from ribosomes through Ca 2+ increase. Conclusion: The results indicate that toxicity of Ca 2+ during brain infarction is correlated with the increase of acrolein. Highlights: Size of brain infarction was decreased by TB34, a channel blocker of NMDA receptors. Levels of Ca 2+ and protein-conjugated acrolein (PC-Acro) were reduced by TB34. Polyamines decreased and PC-Acro increased by Ca 2+ in cell culture systems. 20 to 40 μM Ca 2+ caused the release of polyamines from ribosomes in vitro. Acrolein is produced from polyamines released from ribosomes through Ca 2+ increase.